On the Evolution of Memory: A Time for Clocks - Gerstner, Jason R. (Frontiers in Molecular Neuroscience, 2012)
What was the earliest engram? Biology has evolved to encode representations of past events, and in neuroscience, we are attempting to link experience-dependent changes in molecular signaling with cellular processes that ultimately lead to behavioral output. The theory of evolution has guided biological research for decades, and since phylogenetically conserved mechanisms drive circadian rhythms, these processes may serve as common predecessors underlying more complex behavioral phenotypes. For example, the cAMP/MAPK/CREB cascade is interwoven with the clock to trigger circadian output, and is also known to affect memory formation. Time-of-day dependent changes have been observed in long-term potentiation (LTP) within the mammalian suprachiasmatic nucleus and hippocampus, along with light-induced circadian phase resetting and fear conditioning behaviors. Together this suggests during evolution, similar processes underlying metaplasticity in more simple circuits may have been redeployed in higher-order brain regions. Therefore, this notion predicts a model that LTP and metaplasticity may exist in clock-forming circuits of lower-order species, through phylogenetically conserved pathways, leading to several testable hypotheses.